PERAN PENDIDIKAN KARAKTER DALAM MEMINIMALISIR KENAKALAN REMAJA - Ahnaf Sulthaan Dzakkii; Edy Soesanto; Rendy Kurniawan (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This research aims to describe efforts to minimize juvenile delinquency by using the role of education, the role of parents, the role of the environment or society and the role of peers. The research method used was a quantitative method. The data collection technique used was research carried out in 2 RTs in the community. Harapan Baru Community Health Center area. The selection of settlements is based on the proximity of the residential zone to Nightlife Place (THM). In this case, the THM in question is the RT area that is used as a karaoke place and a place to provide commercial sexual services. This research uses a population sampling technique, which means that the entire population is sampled as many as people, with a sample size of teenagers. Based on the research results, it shows that the majority of respondents who committed delinquency were 104 students aged 13 years and 70 students aged 14 years. The age of 13-14 years is the age of early adolescence, during this phase teenagers are still confused about what actions they should take (Mentari et al., 2018). The most delinquency occurred in RT002 with 170 teenagers because in RT 002 the average teenager was 13-16 years old. Delinquent behavior is mostly carried out by male children because boys have strong behavior and high emotions, so that most male students will commit delinquency when they have problems related to family, girlfriends and so on (Sunaryanti , 2016). The highest amount of delinquent behavior was found in RT002 with a value proportion of 75%, while in RT003 it had a value proportion of 68%. The conclusion from this research is that character education helps teenagers understand and internalize moral values such as honesty, integrity, empathy and responsibility. This provides a strong foundation for good decision making.